Programa Brasil Alfabetizado na UECE: a alfabetização como mediação de inclusão social - Moreira, Rejane Mary (2010)
This study aimed to analyze the contribution of the Brazil Literate Program, run by UECE, regarding the inclusion of students of the fifth-period 2007/2008. Based on this objective we verified if this literacy experience led the students of this class to keep on reading and writing with the appropriate understanding. We decided for the descriptive, qualitative study, and as a technique, a semi-structured interview of which took part 13 literates of three classes of the program, which took place in the neighborhoods of Jardim das Oliveiras, Pio XII and Aerolândia. A questionnaire was carried out with the teachers of these classes and another with the educational coordinator of the project. The results indicate that the experience of literacy performed by UECE did not lead the literates of the fifth class to keep on reading and writing, failing on the acquisition of reading, writing, basic arithmetics and the continuity of these skills used in everyday life, as well as on the studies related to adult education. It is noteworthy, as positive in this program, 'small steps' such as learning how to sign their own names, what means the development of oral language and the appropriation of a new vision of life. Such fact led them to raise self-esteem. The results of the survey suggest that to seek paths or solutions which are favorable to the inclusion through literacy, we must consider the concrete conditions of life of learners and adopt measures of selection for educators in the sense that the initial, continuing and permanent training of those, move towards the establishment of a new teaching with committed, qualified and certified professionals in the area of adult education; an offer which is not of compensatory policies. However, the proposal of EJA policy is able to break up with the practices of old campaigns of assistance, uncommitted with the continuity of schooling and the transformation of society. Such education proposal must consider and respect diversity as a value which is continuing and liberating.